The application of MOHID to assess the potential effect of sewage discharge system at Bahía Blanca estuary (Argentina) - Pierini, Jorge Omar (2008)
The Bahıa Blanca urban wastewater treatment plant (UWWTP) discharges the wastewater from the city into the Bah´ıa Blanca Estuary through a tidal channel located 4 km south from the closest city, Ingeniero White, and 1.7 km south from the mouth of the Napost´a Creek. There are four UWWTPs discharging in the Bah´ıa Blanca Estuary, with the highest flow from the Bah´ıa Blanca UWWTP at 65000 m3 d−1, corresponding to 77% of the total (Heffner et al. 2003). Wastewater is an important source of freshwater in the Bah´ıa Blanca estuary comprising 23.3% of the overall freshwater, with contributions of a similar magnitude as the freshwater inputs from the Napost´a Grande Creek, 86400 m3 d−1 (Carrica 1998) and the Sauce Chico creek, 164000 m3 d−1. Sewerage systems in Bah´ıa Blanca city are designed with overflow structures that discharge into local waterways when the capacity of the system is exceeded. Overflows occur when the hydraulic capacity of the system is exceeded due to heavy rains. During dry periods, overflow can also take place due to blockages or pump failures. Aguas Bonaerenses Sociedad An´onima (ABSA) manages the main network. The aim of this research was to analyze the potential risks of sewage in the estuary and the installation of a new UWWTP on the coast in the inner Bah´ıa Blanca estuary near bathing waters, i.e. the Maldonado Municipal pool.